2015
DOI: 10.7205/milmed-d-14-00601
|View full text |Cite
|
Sign up to set email alerts
|

Research on U.S. Military Women: Recruitment and Retention Challenges and Strategies

Abstract: There are few published articles specific to research recruitment and retention in female military populations. Available resources broadly address recruitment challenges for Veterans, marginalized, hard-to-access, and transient research participants, which may provide guidance and strategies for success when applied to military populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Because recruiting service members for research has been noted to be difficult (Braun et al, ; Bush et al, ; Williams et al, ), it is important to avoid turning away those who actively inquire about their eligibility to participate. We recommend avoiding unnecessarily restrictive criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because recruiting service members for research has been noted to be difficult (Braun et al, ; Bush et al, ; Williams et al, ), it is important to avoid turning away those who actively inquire about their eligibility to participate. We recommend avoiding unnecessarily restrictive criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge about research participants’ decision‐making can improve recruitment and retention strategies that target specific populations and can help facilitate high‐quality research with representative samples. Researchers conducting research relevant to the health needs of military personnel often rely on US military service members to participate in their research but have reported that recruiting service members as research participants is challenging (Braun, Kennedy, Sadler, & Dixon, ; Bush, Sheppard, Fantelli, Bell, & Reger, ; Williams, Gatien, & Hagerty, ). Little is known about the reasons why service members decide to participate in health research studies.…”
mentioning
confidence: 99%
“…This is particularly evident among the nation's 22 million US veterans. Despite a critical need for evidence-based approaches to service-related health issues, veterans are frequently reluctant to partner with or participate in the research enterprise (Bush, Sheppard, Fantell, & Bell, 2013;Braun, Kennedy, Sadler, & Dixon, 2015;Littman, True, Ashmore, Wellens, & Smith, 2018;Williams, Gatien, & Hagerty, 2012;Funderburk, Spinola, & Maisto, 2015). The purpose of this multi-state project was to invite veterans to dialogue about (1) their research priorities; (2) perceived barriers to research participation; (3) recommended strategies for engaging veterans in research; and (4) their preferences for receiving research findings.…”
Section: Introductionmentioning
confidence: 99%
“…While critical for successful research on military health issues, researchers have reported difficulties in recruiting service members as research participants. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Braun et al 3 presented a review of literature that identified recruitment challenges in research with U.S. military women. Their findings indicated that there is limited literature regarding recruitment and retention challenges in research with service members as research participants, and specifically with female service members as research participants.…”
Section: Introductionmentioning
confidence: 99%